ANALYSIS OF COOPERATIVE SOCIETIES, ENTREPRENEURIAL BUSINESS GROWTH AND POVERTY ALLEVIATION IN SOUTH WEST NIGERIA - NWACHUKWU, OFORBUIKE FRANCIS; IBRAHIM, MOHAMMED GADDAFI; LAWAL, KAMALDEEN A.A; ABDULAHI, TAIWO OLABISI (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
Cooperative societies have been increasingly recognized globally as effective mechanisms for promoting entrepreneurship and reducing poverty. This study, titled Analysis of Cooperative Societies, Entrepreneurial Business Growth and Poverty Alleviation in South West Nigeria, examined the pivotal role of cooperative societies in fostering entrepreneurial development and reducing poverty as key drivers of sustainable development in the region. Grounded in the Social Capital Theory, which highlights the importance of social networks, trust, and mutual support, the study utilised a descriptive survey design to gather data from cooperative society members across six state capitals: Ado-Ekiti, Ikeja, Abeokuta, Akure, Osogbo, and Ibadan. A total sample size of 384 was drawn using stratified random sampling from a population of 684,200 registered cooperative members, with 352 valid responses obtained for analysis. Using linear and multiple regression models, the study found that cooperative societies significantly contribute to poverty alleviation (R² = 0.584, β = 0.764) and have an even stronger effect on entrepreneurial business growth (R² = 0.743, β = 0.862). These findings underscore the critical influence of cooperative societies in promoting sustainable economic development in South West Nigeria. The study recommends enhanced policy frameworks to support cooperative societies, including improved access to finance, skill development programmes, and stronger regulatory oversight to maximise their contributions to poverty reduction and entrepreneurial growth